Distal Femoral Oblique Fracture in a Young Male Soldier: Case Report of an Unusual Presentation. Issue 22 (May 2016) - Cohen, David Naji; Al Khateeb, Hesham; Safwat, Mohammed
Abstract : Abstract: Here, we report a case of a distal femoral fracture in a 23-year-old male army cadet who presented to the Accident and Emergency department following a twisting injury while participating in a routine military marching exercise. A pathological fracture was considered but this suspicion was put to rest following thorough investigations, leaving only a diagnosis of a nontraumatic spontaneous femoral fracture. To our knowledge, there have been no reported cases of distal femoral fractures associated with nontraumatic military exercises, with the majority of injuries instead related to stress fractures. A vigilant literature search yielded no cases of similar injury nature, which is the primary reason we believe that those interested in orthopaedics or military doctors would find themselves drawn to this case. The patient presented with severe pain in his left thigh and on examination there was a deformity of his left thigh. In terms of investigations, a bone profile, plain film radiographs, C-reactive protein, erythrocyte sedimentation rate, and tumor markers were all preformed and proved unremarkable. The definitive treatment was by open reduction and internal fixation. Femoral fractures often require significant amounts of force, particularly in young, healthy individuals. Generally, these injuries in this demographic follow high-energy traumas, with the lion's share occurring following a road traffic accident or other high-speed impact. More often than not, the treatment is surgical. Given the extraordinary manner of this such, one must be attentive and exhaustive in their investigation of such presentations.